Assessing the Diagnostic Significance of Herpes Virus Infections' Serological Markers in Children: Overdiagnosis or Clinically Relevant Studies? Retrospective Study - A. A. Ivanov; T. V. Kulichenko ("Paediatrician" Publishers LLC, 2023)
Background. Nowadays, population generally has high contamination with herpes virus infections. Infection commonly is asymptomatic, and the virus persists in the human body over a lifetime. Excessive diagnosis of herpes virus infections as well as overestimation of their role in the genesis of various diseases in immunocompetent people are common in Russian pediatrics.Objective. The aim of the study is to assess the frequency and efficacy of serological testing in the suspected correlation of herpes virus infections and infectious and somatic diseases in a multidisciplinary hospital.Methods. The study included patients hospitalized in the multidisciplinary hospital in Moscow, who were assigned serological examination for herpes viruses. The laboratory study was carried out by enzyme-linked immunosorbent assay with the revealing the markers of herpes simplex virus type 1 and 2, Epstein-Barr virus, and cytomegalovirus. The results of the examination were analyzed according to the nosology and their role in diagnosis and management.Results. The identification of herpes virus infections' markers was performed for 996 patients undergoing medical treatment in 17 different hospital departments within 2 months. Most commonly the examination was prescribed in infectious disease, pediatric, and hematological departments and covered more than 140 different nosologies. Acute respiratory infection, reactive arthritis, thrombocytopenia, infectious mononucleosis, acute tonsillitis, gastrointestinal pathology, acute bronchitis, and pneumonia were the most common nosologies. Positive markers of acute infection were revealed in 1.71% of cases for HSV-1/HSV-2, in 4.89% - for EBV, in 3.81% - for CMV. Moreover, positive results of serological examination were mostly noted in the cases of infectious diseases: infectious mononucleosis, tonsillitis, or acute respiratory infections. Tests were assigned for all three infections at the same time in most cases.Conclusion. Widespread examination for herpes virus infections is the typical variant of overdiagnosis and it is usually less informative. Generally positive markers are observed in typical course of herpes virus infections when clinical picture is enough for diagnosis verification.